2018
DOI: 10.1097/md.0000000000012258
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance or no surveillance for deep venous thrombosis and outcomes of critically ill patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…This is notable because current guidelines in critically ill patients who do not have COVID-19 suggest using pharmacologic prophylaxis alone over combined pharmacologic and mechanical prophylaxis. 47,59 Meanwhile, the guidance document from the AC Forum suggests that in critically ill patients with COVID-19, intermediate or increased intensities of thromboprophylaxis could be used. 55 The authors acknowledge that this was based on expert opinion, and this was published before the results of the INSPIRATION randomized trial were made available.…”
Section: Remarksmentioning
confidence: 99%
“…This is notable because current guidelines in critically ill patients who do not have COVID-19 suggest using pharmacologic prophylaxis alone over combined pharmacologic and mechanical prophylaxis. 47,59 Meanwhile, the guidance document from the AC Forum suggests that in critically ill patients with COVID-19, intermediate or increased intensities of thromboprophylaxis could be used. 55 The authors acknowledge that this was based on expert opinion, and this was published before the results of the INSPIRATION randomized trial were made available.…”
Section: Remarksmentioning
confidence: 99%
“…Among critically ill patients who receive pharmacologic thromboprophylaxis, adjunctive IPC cannot result in a significantly lower incidence of proximal lower-limb DVT than pharmacologic thromboprophylaxis alone. 32 Therefore, once the bleeding risk decreases, the pharmacologic thromboprophylaxis should be resumed as earlier as possible.…”
Section: Risk Factors and Risk Assessment For Venous Thromboembolismmentioning
confidence: 99%
“…Therefore, it can be speculated that immune de ciency may relate to clinical course of COVID-19 and HBV co-infection after receiving corticosteroid therapy. Similarly, observational studies in patients with SARS and MERS demonstrated corticosteroid therapy association with adverse effects including delayed viral clearance from blood and respiratory tract and increased risk of secondary infection 23,24 . Our results were consistent with previous studies and further supported a role of corticosteroids in prolonging SARS-CoV-2 replication in patients with COVID-19 and HBV co-infection.…”
Section: The Decrease Of Immune Cells Especially Lymphocytes Cd4+ T Cells and Cd8+ T Cells Is Indicated Markermentioning
confidence: 97%